2004
DOI: 10.1136/ard.2004.022624
|View full text |Cite
|
Sign up to set email alerts
|

Presence of systemic autoimmune disorders in patients with autoimmune thyroid diseases

Abstract: Objective: To evaluate the prevalence of antinuclear antibodies (ANA) in patients with autoimmune thyroid diseases (ATD) and the presence of systemic autoimmune disorders among ANA positive patients with ATD. Methods: 168 consecutive patients with ATD with positive antithyroid antibodies and 75 healthy subjects were tested for the presence of ANA. ANA positive patients were further evaluated by complete history, physical examination, blood and urine tests, and immunological studies. Patients with subjective xe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 19 publications
3
71
2
2
Order By: Relevance
“…Moreover, in the present study, ANA was positive in 1.7% (1/56) of patients, while in Tektonidou's study 58/168 (35%) patients with ATD were ANA positive [13] and in Lazúrová` s study patients with ATD had higher prevalence of ANA (45%) [14]. Positivity of ANA in the present study was lesser than last studies.…”
Section: Discussioncontrasting
confidence: 67%
“…Moreover, in the present study, ANA was positive in 1.7% (1/56) of patients, while in Tektonidou's study 58/168 (35%) patients with ATD were ANA positive [13] and in Lazúrová` s study patients with ATD had higher prevalence of ANA (45%) [14]. Positivity of ANA in the present study was lesser than last studies.…”
Section: Discussioncontrasting
confidence: 67%
“…It is also known that the identification of anti-Ro/La at the beginning of SS demonstrates that these patients have a greater chance of developing thyroid dysfunction (18) . Tektonidou et al published that SS happens in 1/10 patients with thyroiditis autoimmune who have positive antinuclear antibodies (ANA) (27) , being suggested by others to search in all patients with severe dry eye ( 28) . The data presented in this study, showed that assessments of tear function tests and salivary gland involvement in patients with autoimmune thyroid diseases had no significant differences compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As an autoimmune disease, the specific cause of hyperthyroidism with leukopenia is unclear. Previous studies suggested that GD patients with hyperthyroidism can produce antibodies against leukocyte and antineutrophil cytoplasmic antibody, which results in increased leukocyte destruction (11). Several studies considered the involvement of genetic predisposition in the pathogenesis (12), whereas others suggested that a high level of thyroid hormones causes abnormal leukocyte distribution, namely, leukocytes gather at the edge of the pool.…”
Section: Discussionmentioning
confidence: 99%